1987
DOI: 10.1007/bf00284536
|View full text |Cite
|
Sign up to set email alerts
|

Thallium-201 washout in coronary artery disease using SPECT ? a comparison with coronary angiography

Abstract: In this study, tomographic 201Tl washout analysis and coronary angiography were compared in 100 subjects. Seventeen subjects with healthy coronary arteries were used as reference material, on the basis of which the reference ranges for both the total washout of the heart muscle and the regional washout were determined. With angiography as the standard, this material yielded the following sensitivity values for total myocardial washout: 80% for three vessel proximal disease (n = 30), 64% for peripheral three ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…This could be explained in 10 patients by ischemia produced by a more severe obstruction in another artery, either a stenosis in RCA or a branch stenosis in LAD or LCX. With quantitative evaluation higher values for sensitivity and specificity have been obtained for 201TI SPECT (5,8,10,11,15,17,19,20,24).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained in 10 patients by ischemia produced by a more severe obstruction in another artery, either a stenosis in RCA or a branch stenosis in LAD or LCX. With quantitative evaluation higher values for sensitivity and specificity have been obtained for 201TI SPECT (5,8,10,11,15,17,19,20,24).…”
Section: Discussionmentioning
confidence: 99%
“…This study and many others (2,6,7,11,18,26,28) have demonstrated that 201Tl SPECT is a sensitive method for the detection of coronary disease. SPECT does not, however, always indicate the total extent of the disease.…”
Section: Relationship Between Severity Of Coronary Artery Lesions Lementioning
confidence: 51%
“…The code system was adapted from the American Heart Association (AHA) reporting system (I). An arterial lesion was considered significant if the diameter was reduced by 50 per cent or more (6,7,12,18,25,29). Left main stem stenoses were reported as stenotic lesions of the same degree in both LAD and LCX.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomographic wash-out analysis added 10% of sensitivitv to visual analysis of 2 0 1 T1 SPECT (13). It is less sensitive than evaluating perfusion defects (8).…”
Section: Disciissionmentioning
confidence: 99%